Consequences of Chronic Non-Cancer Pain in adulthood. Scoping Review. - Rocío Cáceres-Matos; Eugenia Gil-García; Sergio Barrientos-Trigo; Ana María Porcel-Gálvez; Andrés Cabrera-León (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To examine and map the consequences of chronic pain in adulthood. METHOD Documents addressing the impact of chronic pain on the psychological and social spheres of people suffering from chronic pain, published in Spanish and English between 2013 and 2018, were included. Those who addressed pharmacological treatments, chronic pain resulting from surgical interventions or who did not have access to the full text were excluded. Finally, 28 documents from the 485 reviewed were included RESULTS Studies show that pain is related to high rates of limitation in daily activities, sleep disorders and anxiety-depression spectrum disorders. People in pain have more problems to get the workday done and to maintain social relationships. Chronic pain is also associated with worse family functioning. CONCLUSIONS This review shows that limitations in the ability to perform activities of daily living, sleep, psychological health, social and work resources and family functioning are lines of interest in published articles. However, knowledge gaps are detected in areas such as the influence of having suffered pain in childhood or adolescence, the consequences of non-fulfillment of working hours and gender inequalities.